KNOWLEDGE, BELIEFS, AND ATTITUDE TOWARDS SICKLE CELL DISEASE AMONG SENIOR HIGH SCHOOL STUDENTS IN TAMALE METROPOLIS - Baba, P.; Yidana, A. (UDS International Journal of Development, 2023)
Sickle cell disease (SCD) is a hereditary disease that comes with many complications, such as vaso-occlusive crises and anemia. The SCD is now a public health problem due to its global spread. As a result, the incidence of it in Ghana has increased drastically over time. The research was conducted among Senior High School students from Forms 1-3 to assess their knowledge, beliefs and attitude towards SCD. The data collection was carried out in four selected schools in the Tamale Metropolis. Participants engaged in the study were 386 and their ages ranged from 15 to 24 years, with a mean of 17.94 years (SD: 6.28). About 47% of the students were in the 18 - 20 age range, the 23-24 age range accounted for 3.11% of the entire sample, the 15-17 age range was 44.30%; and 21-22 age range was 5.44%. Eighty one per cent (81.0%) of the participants have heard of SCD with just a few of them (11.66%) knowing their sickle cell status. Some 31% perceived SCD as curable; while 30.05% perceived it as not curable. However, 18.13% and 20.47% reported that they were not sure or did not know whether SCD is curable or not, respectively. A large number of them (48.70%) indicated they would seek spiritual intervention when they have SCD. The beliefs of students on SCD included the belief that SCD is acquired at birth (72.28%), through sexual intercourse (20.21%, 78), spiritual means (13.47%) or it is airborne (3.37%), and through food (1.5%). Regarding their attitudes toward SCD, 88.34% had not been screened for SCD, and the reasons assigned included not falling sick easily (22.22%), and not considering it as necessary (14.53%), as well as the fear of testing positive (13.11%). It was concluded, even though most participants had heard about SCDs, only a few knew their SCD status. There was a statistically significant associations between the student's class and knowledge of SCD and the course of study. Participants believed that the SCD can be transmitted at birth or through sexual intercourse, airborne, food and spiritually. Generally, there was poor attitude towards SCD by students.Keywords: Knowledge, Beliefs, Attitude, Sickle Cell, Disease